Co-Occurrence and Co-Authorship Analysis in Vocabulary Acquisition - Ni Putu Meira Purnama Yanti (Jurnal Multidisiplin West Science, 2022)
This study aims to explore the current status of publications in the year, the keywords of research hotspots, the co-occurrence of the keywords, and the co-authorship. It is analyzed a total of 1.494 references which were downloaded from the Scopus. The VOS-viewer software is used for the analysis. Many results regarding the annual trends, the keywords distribution, the co-occurrence of keywords in ten clusters, the country and institute co-authorship, the most cited VA associated publications, also the reference and journal co-citation are presented in this paper. This study shows the development status and trends on vocabulary acquisition. It can help people and the academic researchers to get comprehensive understanding about the vocabulary acquisition. It also has reference values for the research and application of the vocabulary acquisition (VA) visualization methods.